Detection of the biofilm among uropathogenic bacteria and measurement of procalcitonin of urinary tract infections among Iraqi children - Raghad Abdulwahab Kadhim B.Sc. Biology/ College of Science / University of Baghdad (2020); Supervised by Assistant Professor Dr. Sanaa Khudhur Jameel Ph.D. Medical Microbiology (2025)
Urinary tract infections (UTIs) are a serious public health concern which causes by a variety of microorganisms. UTI are caused by bacteria, but in rare cases may be due to fungi and viruses. In microbiology, Urinary tract infection can by classified as the presence of a pure bacterial growth >105 colony forming units/ml in urine after it passes through the renal tubular system, pelvis, ureters, bladder, and urethra. Females are more likely to become infected with UTI compared to men and this to physioanatomical changes. The current study's goal was to determine the most common causative agents of UTI in children, establish the utility of procalcitonin for predicting UTI among children, and to detect the activity of silver nanoparticles as antibacterial agents The current study was conducted on 120 urine and blood samples collected from children (three years to twelve years old) from different areas in Baghdad, during the period September 2022 to January 2023 at Al-Imamain Al-Jawadain Medical City and Central Teaching Hospital of Paediatrics. The current study included to types of samples: urine samples for isolation and identification of bacteria, and biofilm detection by microtiter plates. Blood samples for haematological study and immunological study. The results show the presence of different types of bacteria which cause urinary tract infection, such as Escherichia coli the most common (51.66%), Klebsiella pneumonia (18.33%), Proteus mirabilis (11.68%), Staphylococcus aureus (6.66%), Staphylococcus epidermidis (6.66%), Enterococcus faecalis (3.35%) and Staphylococcus haemolyticus (2.27%). Gram-negative were the most common bacteria that cause UTI. The study also showed that the antibiotic Meropenem and Imipenem were the most effective against bacterial isolates while amoxicillin was the least one as it showed resistance against most of the isolated bacteria. I Abstract Biofilm was detected by Quantitative assay by using microtiter plate and from total 60 isolate only 38 were biofilm forming, and the results were 29.88% of the isolates have the ability to form strong biofilm, 33.20% were moderate and 36.52% were none or weak biofilm forming. The strong biofilm formation percentage of E. faecalis, Proteus spp., K. pneumonia, S. aureus and E. coli isolates were (100%, 57.1%, 45.4%, 25.0 % and 19.4% respectively), while he moderate biofilm formation percentage of S. haemolyticus, S. epidermidis, S. aureus, Proteus spp., K pneumonia and E. coli were (100%, 50.0%, 50.0%, 28.6 %, 27.3% and 32.2% respectively). In the present study, silver nanoparticles showed a good antibacterial activity against most of the isolates. This test done by using microtiter plate to measure the activity of silver nanoparticles after 24 hours incubation, the result was highly significant with P value (P≤0.01). The immunological parameters of procalcitonin serum level were measured by using ELISA reader, and the result showed significant differences when compared with the healthy individuals. Procalcitonin serum level was highly significant with P value. Concluded from this study that most of UTI in children are due to gram negative bacteria, and the most common were E.coli , and most of the bacteria isolate were able to form biofilm also, the silver nanoparticles showed a high activity as antibacterial agents, and finally there was an increased in serum level of procalcitonin and CRP in patients. II